Pričakovanja partnerjev o starševski vlogi v času nosečnosti - Guštin, Katja (Psihološka obzorja (Ljubljana), 2009)
The aim of our study was to explore what pregnant couples expect of their parenting role and how their expectations are related to partnership satisfaction. In accordance with the snowball effect principle and in cooperation with the School for Parents in Ljubljana, we included 90 couples, who were expecting a child, into our study. They filled out Survey concerning their expectations about parenting roles, where they evaluated how often they and their partners would be carrying out a given action in the first three years after the birth of the child and Relationship Satisfaction Survey (Gaultiere, 1995). We have established that men and women expect higher participation in the parenting role for mothers. It seems that women are taking over a part of the male parenting roles. Research results shows that higher relationship satisfaction is positively associated with stronger division of parenting tasks between the partners. We are assuming that men are the least active at routine chores in connection with their child, therefore their higher participation or equal participation of both partners has positive influence on partnership satisfaction.
Keywords: human pregnancy; nosečnost; starševstvo; pričakovanja; vloge; partnerstvo; medosebni odnosi